The Sun, 24 Jun 2008 - Charles Ramendran (Sun Media Corp.Sdn.Bhd., 2008)
A policeman was arrested on Sunday for allegedly raping a 17-year-old student at police station at Taman Putra Heights in USJ Subang Jaya last week.